The Effect of Using Mentimeter Media in Learning to Improve News Text Comprehension in Grade XI Students - Ido Parningotan Sitinjak; Elza Leyli Lisnora Saragih; Pontas Jamaluddin Sitorus (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Interactive and innovative learning media are essential in learning to achieve high learning outcomes. Mentimeter is a web-based presentation platform and application designed to create interactive presentations in real-time. This tool allows users to create polls, quizzes, word clouds, and question and answer sessions to increase student engagement in the classroom. This study aims to describe: 1) the results of the pre-test on the ability to understand news texts; 2) the results of the post-test on the ability to understand news texts; 3) the effect of Mentimeter media on learning the ability to understand news texts. The research method used is a quantitative method through a One Group Pretest–Posttest Design. This study took place in the first semester of the 2025/2026 academic year at SMA Negeri 1 Tanjung Morawa. The population of this study was 32 grade XI students who took the pre-test, learning to understand news texts using Mentimeter media, and took the post-test. The sample was determined at 30 based on a statistical formula; selected by simple random selection without replacement. Data on the ability to understand news texts were collected using a test instrument compiled based on objective indicators to produce test specifications for the ability to understand news texts as a basis for compiling test items. The data were analyzed using a one-sample t-test to achieve the first and second objectives. A paired sample t-test was used to determine the third learning objective. The use of the t-test can be justified because the homogeneity and normality tests were met. The results of the study: 1) the pre-test results of the ability to understand low-category news texts; 2) the post-test results of the ability to understand high-category news texts; 3) the mentimeter media had a significant effect on learning the ability to understand news texts.